Rural marketing : targeting the non-urban consumer - Velayudhan, Sanal Kumar, 1955- (Response Books, 2007)
This highly practical and informative book provides unique insights into the essential. features of rural markets in India as well as challenges posed by the rural consumer. Retaining the managerial perspective of the first edition, this second edition. has been thoroughly revised and expanded, and examines in greater detail the concept. of rural markets and rural marketing. It also contains numerous short cases to. illustrate how social and cultural habits influence rural consumer behaviour. The book contains comprehensive insights into:. - The nature and patterns of rural behaviour. - A deta.